Liquisolid systems: Evaluation of the influence of formulation variables on the optimum liquid load - Aleksić, Ivana; Glišić, Teodora; Cvijić, Sandra; Parojčić, Jelena (Archives of Pharmacy, 2022)
Liquisolid systems represent an emerging approach in the preparation of solid dosage forms with liquid lipophilic drug or poorly water-soluble drug solution/suspension in suitable liquid vehicle. This study addresses the lack of data regarding the compaction behavior of liquisolid systems, with the aim to investigate the influence of liquid load, carrier to coating ratio, carrier type (microcrystalline cellulose vs. spray dried calcium hydrogen phosphate, anhydrous (Fujicalin®)) on flowability and compaction properties of liquisolid systems and to determine the optimum liquid loads. Liquisolid admixtures with Fujicalin® showed notably better flowability than those with microcrystalline cellulose. An increase in carrier to coating ratio led to enhanced flowability of the admixtures. Compacts with Fujicalin® had good mechanical properties up to 24.7% liquid, while those with microcrystalline cellulose had acceptable mechanical strength up to 16.2% liquid. Liquisolid systems with Fujicalin® showed similar tabletability profiles as those with microcrystalline cellulose, despite having higher liquid content. The ejection stress values indicated that the addition of lubricant might be needed in the case of liquisolid systems with Fujicalin®. Superior properties of Fujicalin® as a carrier for liquisolid tablets were revealed, and dynamic compaction analysis was found to be a valuable tool for the assessment of compaction behavior of liquisolid systems.
Keywords: liquisolid compacts; tabletability; dynamic compaction analysis; Fujicalin®; microcrystalline cellulose